PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. BANK SULSELBAR CABANG BANTAENG - Almunawwar, Fahruni; Arniati, Arniati; Rasyid, Muh Nur (LPPM - STIE SAKTI ALAM KERINCI, 2025)
This study aims to examine the influence of work discipline and work environment on employee productivity at PT. Bank Sulselbar Bantaeng Branch. The research uses a quantitative approach with a saturated sampling technique involving the entire population of 37 employees. Data collection was carried out through the distribution of questionnaires using a Likert scale as a measurement tool. The data obtained were analyzed using multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that work discipline and work environment have a positive and significant effect on employee productivity. This is evidenced by the t-values for work discipline (2.234) and work environment (3.109), both of which are greater than the t-table value of 2.035, with significance levels below 0.05. Based on these findings, it can be concluded that strong work discipline and a conducive work environment can optimally enhance employee productivity. Keywords: Work Discipline, Work Environment, Employee Productivity.